2021
DOI: 10.22270/ajprd.v9i3.966
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of immune mechanisms during hepatoprotective effects of Dawa-Ul-Kurkum, a Unani polyherbal preparation in experimental model of paracetamol induced liver damage in rats

Abstract: Objective: Iimmunomodulatory effects of Dawa-Ul-Kurkum, a Unani polyherbal preparation and the possible mechanisms in experimental model of paracetamol induced liver damage in rats. Materials and methods: The drug Dawa-Ul- Kurkum has been prepared and provided by CRIUM, Hyderabad. Silymarin was purchased from Sigma-Aldrich (USA) and paracetamol (marketed by Cipla LTD) purchased from general pharmacy shop. Biochemical kits were purchased from ERBA Diagonostic Mannheim Gmbh. Serum alanine aminotransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…While the study confirmed the ability of vitamin e with the plant extract to reduce fat oxidation and improve the antioxidants of glutathione and this study agreed with, that the water extract of leaves of plant has antioxidants So effective vitamin e supplementation with these compounds reduced MDA levels and increased antioxidant enzymes levels (35). This result is in agreement with a study performed by Wesam and Amira (31), Rafi et al (36).…”
Section: Discussionsupporting
confidence: 91%
“…While the study confirmed the ability of vitamin e with the plant extract to reduce fat oxidation and improve the antioxidants of glutathione and this study agreed with, that the water extract of leaves of plant has antioxidants So effective vitamin e supplementation with these compounds reduced MDA levels and increased antioxidant enzymes levels (35). This result is in agreement with a study performed by Wesam and Amira (31), Rafi et al (36).…”
Section: Discussionsupporting
confidence: 91%